2017
DOI: 10.1097/htr.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Structural Connectivity Related to Persistent Symptoms After Mild TBI in Adolescents and Response to Aerobic Training: Preliminary Investigation

Abstract: OBJECTIVE To quantify structural connectivity abnormalities in adolescents with mild traumatic brain injury (mTBI) and to investigate connectivity changes following aerobic training using graph theory and diffusion tensor imaging (DTI) tractography. SETTING Outpatient research setting. PARTICIPANTS Twenty two children (age: 15.83±1.77 years, 10 F) with 4–16 weeks of persistent symptoms after mTBI and a matched healthy comparison group. DESIGN Randomized clinical trial of aerobic training and stretching c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 19 publications
(22 reference statements)
4
31
0
Order By: Relevance
“…In one study, p-values and t-scores were used to estimate the effect size (Hellyer et al, 2015). For longitudinal GTA studies (Yuan et al, 2017a;Yuan et al, 2017b), only the baseline ('pre-training') comparisons between TBI and HCs were included. Two papers reported TBI connectivity data in separate subgroups, one according to severity level (Königs et al, 2017), and the other by post-traumatic complaints (van der Horn et al, 2016).…”
Section: Data Extraction For Quantitative Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, p-values and t-scores were used to estimate the effect size (Hellyer et al, 2015). For longitudinal GTA studies (Yuan et al, 2017a;Yuan et al, 2017b), only the baseline ('pre-training') comparisons between TBI and HCs were included. Two papers reported TBI connectivity data in separate subgroups, one according to severity level (Königs et al, 2017), and the other by post-traumatic complaints (van der Horn et al, 2016).…”
Section: Data Extraction For Quantitative Synthesismentioning
confidence: 99%
“…Six studies reported on small-worldness differences between TBI and HCs (Caeyenberghs et al, 2012;Caeyenberghs et al, 2014;Hellyer et al, 2015;Yuan et al, 2017a;Yuan et al, 2015;Yuan et al, 2017b), with no significant effect size overall; however, a trend was evident for larger values in TBI patients (g =0.794, p =0.06, I 2 =89.736%). Of the 158 patients in this analysis, 105 were moderate to severe; 108 acute patients were between 96 hours and 5.5 months post-injury, while 50 chronic patients were on average 4.6 years post-injury; and 84 were adults (average age: ~26.6 years) and 74 were paediatric (average age: ~11.8 years) at injury.…”
Section: Small-worldnessmentioning
confidence: 99%
See 2 more Smart Citations
“…In adolescents presenting TBI, global efficiency level, mean local efficiency scores, modularity, normalized clustering coefficient expression, normalized characteristic path length, a measure of structural connectivity abnormality, and small-worldness assessments, as well as Post-Concussion Symptom Inventory scoring, were all inferior to healthy control adolescents, but following aerobic training, global efficiency level was increased and normalized characteristic path length was decreased [25]. Also, the enhanced PostConcussion Symptom Inventory scores were correlated significantly with the global efficiency level improvements and normalized characteristic path length decrease.…”
Section: Introductionmentioning
confidence: 99%